2014
DOI: 10.1186/1745-6215-15-396
|View full text |Cite
|
Sign up to set email alerts
|

The Tinnitus Retraining Therapy Trial (TRTT): study protocol for a randomized controlled trial

Abstract: BackgroundSubjective tinnitus is the perception of sound in the absence of a corresponding external sound for which there is no known medical etiology. For a minority of individuals with tinnitus, the condition impacts their ability to lead a normal lifestyle and is severely debilitating. There is no known cure for tinnitus, so current therapy focuses on reducing the effect of tinnitus on the patient’s quality of life. Tinnitus retraining therapy (TRT) uses nonpsychiatric tinnitus-specific educational counseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The TFI is being utilized in numerous clinical trials, including in the United Kingdom (Fackrell et al, 2013), New Zealand (Chandra, 2013), and the United States (Scherer et al, 2014;Henry et al, 2015). Because of this high level of interest, it is important to provide general guidelines for administering the TFI and for interpreting results.…”
Section: Use Of Tfi In the Clinic And Clinical Researchmentioning
confidence: 98%
“…The TFI is being utilized in numerous clinical trials, including in the United Kingdom (Fackrell et al, 2013), New Zealand (Chandra, 2013), and the United States (Scherer et al, 2014;Henry et al, 2015). Because of this high level of interest, it is important to provide general guidelines for administering the TFI and for interpreting results.…”
Section: Use Of Tfi In the Clinic And Clinical Researchmentioning
confidence: 98%
“…Participants with a flat audiogram were more likely to respond positively to the intensive sound masking intervention than those with a HFSS audiogram but there was no relation to an average hearing threshold profile. To our best knowledge, no previous study has investigated the influence of audiometric configuration on the outcome of tinnitus intervention, even though the study by Chang et al 26 showed that patients with a flat pattern audiogram benefited more from hearing aids compared with those with rising or decreasing audiogram in terms of improvement of psychological handicap and quality of life. The present result is likely to be due to tinnitus characteristics together with their associated hearing status.…”
Section: Discussionmentioning
confidence: 99%
“…The TRTT protocol has been previously described [9]. Briefly, we assessed the efficacy of TRT and its component parts, TC and ST, compared with SOC in habituating the perceived magnitude, perception, and negative emotional reactions to tinnitus.…”
Section: Trtt Trial Designmentioning
confidence: 99%
“…Steps we implemented to address adherence design included engagement of experts to develop standardized protocols, development of checklists, and decisions regarding the number of audiologists and how they were expected to administer treatment within the trial. The TRTT engaged two audiologic experts, one each in TC [9] and SOC [10], to develop the protocols for counseling in the TRTT and serve as protocol monitors. The protocol monitors developed the protocol, trained audiologists, and monitored the quality of the administration of counseling sessions.…”
Section: Design Of Steps For Adherencementioning
confidence: 99%